Relación entre el gasto público en electrificación y el acceso a los servicios de electricidad en la zona rural de la región de Loreto 2014–2023 - Alvan Rurange, Piero Antonio (2025)
The present research analyzes the relationship between public spending on electrification and access to electricity services in rural areas of the Loreto region during the period 2014-2023. Rural electrification is essential for improving living conditions and promoting socioeconomic development in remote areas, where geographical dispersion and natural barriers hinder the expansion of electrical infrastructure. Through a quantitative approach, regression models and correlation analysis are employed to assess the impact of public investments in energy generation, transmission, and distribution. The results reveal a positive and significant relationship between increased spending on electrification and access to electricity services. The impact of spending on distribution stands out, being the component with the greatest effect on improving coverage. Additionally, limitations related to logistical complexity and population dispersion are identified, affecting the efficiency of projects. The study concludes that electrification not only reduces access gaps but also drives economic activity, enhances education, and contributes to poverty reduction. Finally, strategies such as the use of renewable energy and energy education programs are proposed to maximize the social and economic benefits of electrification in Loreto.